Thermospheric Expansion Associated With Dust Increase in the Lower Atmosphere on Mars Observed by MAVEN/NGIMS. Issue 7 (6th April 2018) - Liu, Guiping; England, Scott L.; Lillis, Robert J.; Withers, Paul; Mahaffy, Paul R.; Rowland, Douglas E.; Elrod, Meredith; Benna, Mehdi; Kass, David M.; Janches, Diego; Jakosky, Bruce
Abstract: We present for the first time the dramatic variations in atmospheric composition and density at high altitudes from 170 to 220 km in Mars' neutral thermosphere in response to dust increases in the lower atmosphere, observed by the in situ Neutral Gas Ion Mass Spectrometer onboard the Mars Atmosphere and Volatile EvolutioN satellite. The observations reveal that CO2, Ar, N2, CO, and O densities all increase up to 200% compared to the longer‐term running median densities. The density increases are seen throughout this altitude region, and the relative variations are seen to be stronger at higher altitudes. Density increases indicating the solar extreme ultraviolet influence are also seen. This study is consistent with that during increased dust load, the whole atmosphere expands and rises, and other processes may also be involved. The results agree with the general circulation model predictions, providing observational evidence for how dust increases affect different atmospheric species in the thermosphere. Key Points: This is the first study of dust effects on atmospheric composition and density at high altitudes from 170 to 220 km using MAVEN Atmospheric densities including major and minor species increase strongly in response to dust increase in the lower atmosphere The observed density increases are due to hydrostatic expansion of the thermosphere and also involve other processes